1991
DOI: 10.7326/0003-4819-114-9-735
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Use and Peptic Ulcer Disease: Role of Nonsteroidal Anti-inflammatory Drugs

Abstract: Discrepant findings among earlier studies regarding steroids and the risk for peptic ulcer disease could in part be due to differences in the use of NSAIDs among study participants. The high risk for peptic ulcer disease associated with combined use of NSAIDs and corticosteroids indicates the need to prescribe this drug combination cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
210
0
15

Year Published

1992
1992
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(237 citation statements)
references
References 28 publications
7
210
0
15
Order By: Relevance
“…The combined use of glucocorticoids and nonselective NSAIDs is known to increase the likelihood of upper gastrointestinal problems (20,21). Stepwise logistic regression was used to determine the influence of glucocorticoid therapy, older age, and disease activity on the prescription of NSAIDs (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined use of glucocorticoids and nonselective NSAIDs is known to increase the likelihood of upper gastrointestinal problems (20,21). Stepwise logistic regression was used to determine the influence of glucocorticoid therapy, older age, and disease activity on the prescription of NSAIDs (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Both positive and negative associations between the use of glucocorticoids and gastrointestinal bleeding have been found (20,(23)(24)(25)(26). Although the investigations of gastrointestinal side effects of glucocorticoid therapy alone revealed inconsistent results, current evidence indicates a risk of peptic ulcer up to 15 times greater in patients concurrently receiving glucocorticoids and NSAIDs (20). Therefore a combination of these 2 agents has not been recommended unless carefully monitored low-dose glucocorticoid therapy is administered (27).…”
mentioning
confidence: 99%
“…All patients on a combination of NSAID and corticosteroid should be prescribed gastroprotection as there is a 15-fold increase in the risk of gastric irritation [17]. The attitudes among the physicians showed that this was not common knowledge since only 65% of the respondents prescribed gastroprotectors to more than 75% of their patients with this combination.…”
Section: Assessed Effectmentioning
confidence: 99%
“…No entanto, vale dizer que Chrischilles et al (1990) 16 , num estudo de prevalência e características do uso de múl-tiplos analgésicos entre idosos, evidenciaram que as mulheres idosas com história de úl-ceras utilizavam concomitantemente salicilatos e outros AINE numa freqüência maior do que aquelas não portadoras de úlceras, apesar do risco aumentado de efeitos adversos gastrintestinais nestes indivíduos. O fato de 15,7% dos pacientes do nosso estudo que tinham antecedentes de úlcera e/ou hemorragia utilizarem AINE levanta questões sobre a qualidade deste uso, bem como sobre a existência de monitoramento destes pacientes, o que pode ser objeto de investigações futuras O estudo da associação entre o uso de corticosteróide e o uso de AINE foi motivado pela interação destes dois fatores no aumento do risco de lesões e complicações de lesões do trato gastrintestinal 19 , a exemplo do que ocorre com a história prévia de úlce-ra ou hemorragia. No presente estudo, embora a freqüência geral do uso de corticosteróide tenha sido baixa (3,0%), entre estes usuários o uso concomitante com AINE foi alto (75,0%), ocorrendo o uso conjunto crô-nico em 47,0% dos usuários de corticosteróide.…”
Section: Tabela 5 -Resultados Finais Da Análise Multivariada Dos Fatounclassified
“…Neste sentido, é necessário observar que, se o nú-mero de medicamentos utilizados servir como um indicador do estado de saúde da população estudada, nosso achado pode sugerir que este maior uso de medicamentos representa um maior nível de morbidade da população ou ainda a existência de doenças subjacentes crônicas ou mais complicadas que, em algumas situações, aumentam o risco destes indivíduos sofrerem problemas gastrintestinais 19 . Por outro lado, se o número de medicamentos utilizados significar em algumas situações não um estado precário de saúde, mas, acima de tudo, um sobreconsumo de medicamentos, configura-se então mais um cenário extremamente propício para a ocorrência de interações medicamentosas e reações adversas, principais problemas da polifarmácia.…”
Section: Tabela 5 -Resultados Finais Da Análise Multivariada Dos Fatounclassified